Spatial Analysis of Antenatal Care and Low Birth Weight against Neonatal Mortality Rate in Aceh Province, Indonesia - Nurjannah Nurjannah; Marisa Marisa; Etika Sari (Tehran University of Medical Sciences, 2022)
Background: Similar to Indonesia, Aceh Province also showed a slight decline in neonatal mortality rate. However, the rate is still high compared to other provinces. Efforts to reduce neonatal mortality rate are essential because neonatal deaths contributed up to 71% of all under-five deaths in 2017 in Aceh. Antenatal care and low birth weight are known to be associated with neonatal mortality. The purpose of this study was to map district-level neonatal mortality rate and its determinants (antenatal care and low birth weight) in Aceh to inform policymakers in planning the interventions. Methods: This was a cross-sectional study using publicly available secondary data obtained from Aceh Provincial Health Office. The study used the 2017 data of neonatal mortality rate, percent of 4th antenatal care visit and percent of low birth weight at district level. Thematic maps were produced using ArcMap (V.10.5). The correlation was analyzed using the Spearman rank test. Results: The results indicated the regional variation of neonatal mortality rate across Aceh Province. Districts in the Southern region had lower neonatal mortality rates compared to others. Low birth weight was positively correlated with neonatal mortality rate at district level (Spearman's Rho=0.545, P=0.007). However, the percent of 4th antenatal care visit at district level was not correlated with neonatal mortality rate (Spearman's Rho= -0.35, P=0.097). Conclusion: The study identified regional variations of neonatal mortality rate, low birth weight and ante natal care visit.